Risk‐Sharing or Risk‐Taking? Counterparty Risk, Incentives, and Margins - BIAIS, BRUNO; HEIDER, FLORIAN; HOEROVA, MARIE (Journal of Finance, 2016)
ABSTRACT Derivatives activity, motivated by risk‐sharing, can breed risk‐taking. Bad news about the risk of an asset underlying a derivative increases protection sellers' expected liability and undermines their risk‐prevention incentives. This limits risk‐sharing, creates endogenous counterparty risk, and can lead to contagion from news about the hedged risk to the balance sheet of protection sellers. Margin calls after bad news can improve protection sellers' incentives and in turn enhance risk‐sharing. Central clearing can provide insurance against counterparty risk but must be designed to preserve risk‐prevention incentives.